Intention and Oral Health Behavior Perspective of Islamic Traditional Boarding School Students Based on Theory of Planned Behavior - Taufan Bramantoro; Eris Basiroh; Titiek Berniyanti; R. Darmawan Setijanto; Wahyuning Ratih Irmalia (Association of Support to Oral Health Research (APESB), 2022)
Objective: To analyze the correlation of the students in an Islamic boarding school intention toward oral health behavior by means of the Theory of Planned Behavior (TPB) approach. Material and Methods: A cross-sectional analytic study was conducted on 153 students of an Islamic boarding school who fulfilled the criterion. Data were obtained by a questionnaire and clinical examination. Data were presented as mean and standard deviation. Results: The highest score of the variable that affects behavior recorded from both male and female respondents was Subjective Norm (57.288 ± 12.828), followed by Attitude (25.627 ± 4.144). Meanwhile, the lowest score that affects behavior was Oral Health Knowledge (3.179 ± 1.402). All study variables, according to the theory of planned behavior, such as knowledge, attitude, subjective norm, perceived behavior control, and intention had significant value to predict and assess behavior with p<0.05. Conclusion: Attitude, subjective norms, perceived behavioral control, and oral health knowledge in Private Boarding School's Santris influence the intention to improve oral hygiene behavior.